Double portrait of George and Nelly Gross. From the correspondence of Jacques Gross and Elisabeth Gross-Fulpius with Nettlau
Double portrait of George and Nelly Gross. From the correspondence of Jacques Gross and Elisabeth Gross-Fulpius with Nettlau.